Neem Gum Based Solid Dispersion in Development of Aceclofenac Tablet with Enhanced Bioavailability - Nagpal, Manju; Aggarwal, Geeta; Sharma, Pratima; Mahan, Paramjot; Thakur, Gurjeet S. (Drug Delivery Letters, 2017)
Objective: The main aim of this study was to improve bioavailability of aceclofenac using neem gum as water soluble carrier for the development of solid dispersion based dosage form of the drug. Methods: Solid dispersions (SD) of aceclofenac were prepared by solvent evaporation technique and in the form of co-grinding mixture (CGM). Four batches of neem gum based solid dispersions of aceclofenac were prepared by varying the drug polymer ratio (1:1, 1:2, 1:3 and 1:5). Prepared solid dispersions were evaluated for solubility, FTIR, DSC, X-RD, SEM and in vitro release and the optimized batch was utilized to develop solid dosage form in the form of tablet. The final dosage form (tablet of neem gum based solid dispersion) was evaluated for physicochemical characterization, in vitro release and in vivo pharmacodynamic studies. Results: Solubility studies indicated 1:3 drug to neem gum ratio for the formulation of solid dispersion of drug. CGM also indicated improved solubility of drug. FTIR studies indicated no interaction of drug to polymer (presence of characteristic peaks of drug). DSC and X-RD studies indicated transition from crystalline to amorphous state of drug. SEM images of dispersion showed change in surface characteristics of drug particles in solid dispersions as compared to pure drug (crystallinity of pure drug). In vitro release studies revealed enhanced dissolution rate in solid dispersion (SD1 to SD3) and solid dispersion based tablet (T1) as compared to 47% in case of pure drug. Results of in vivo pharmacodynamic studies indicated faster analgesic potential and efficacy of optimized solid dispersion based tablet formulation than that of pure drug and marketed formulation. Conclusion: The solubility, drug release and in vivo results suggested applicability of neem gum as a prospective carrier of poorly soluble drugs.
Keywords: solid dispersion